Entre mortes e monstros: a insurgência do ato criador - Silva, Karina Pereira Jacob da (2014)
Written through invention of some experiences brought from the theatrical practice, I will try, in this work, to draw a parallel among the act of an artistic creation, the birth of monsters and the experience of death. Therefore, it is necessary to observe the lines of forces that cross these processes, sometimes allowing creation of new territories and ways of operating life, sometimes blocking these flows. Life and art merge by establishing the aesthetic experience of life. In this context, insightful listening from these experiences, such as in the clinical experience, allows the research into new ways of producing subjectivity which are able to establish important reverberations, through actions at the level of micropolitics, that extend to the macropolitic level. The perception of cartographic lines that compose these experiences of artistic creations works questioning the Art institution and its artistic way of dealing with the potential of life